Percentage of time in therapeutic range and proportion of thromboembolic event in nonvalvular atrial fibrillation patient on warfarin - Mohd, Fahmi Nazrin (2015)
Background Atrial fibrillation ( AF ) is the most common sustained cardiac arrhythmia. The use of warfarin reduces the rate of ischemic stroke in patients with nonvalvular AF, but requires frequent monitoring and dose adjustment. Target INR are frequently not achieved, and the risk of thrombosis, bleeding and death may be related to INR control. Methods : We analyzed the relationship between the INR control and the proportion of thromboembolic event, bleeding and clinical factors associated with time in therapeutic range ( TTR ) , among 73 patients with nonvalvular atrial fibrillation. Patient were divided into 2 groups ( those with good control TTR ≥ 60% and those with poor control TTR < 60 % ), according to the percentage time with an INR of 2.0 to 3.0. Outcomes were compared according to INR control. The main outcome measures were thrombotic event, and bleeding. Result : The mean TTR in Kelantan patient is 40% with poor control group had higher rates of bleeding ( odds ratio, 5.01; 95% CI 1.30 to 19.39; p = 0.02 ) compared with the good control group. Several clinical factors were identified incliding triglyceride ( odds ratio, 10.60;95% CI 1.64 to 68.39; p = 0.013 ), type of AF – permanent ( odds ratio, 6.81; 95% CI 1.22 to 38.11; p = 0.029 ) and bleeding ( odds ratio, 9.98; 95% CI 1.65 to 60.22; p = 0.012 ) significantly associated with TTR < 60%. Conclusion : In patient with nonvalvular atrial fibrillation taking warfarin, the risk of bleeding is related to poor control of TTR. Good INR control is important to improve patient outcome.